Physical and sensory characteristics of sourdough bread enriched with beetroot (Beta vulgaris L.) powder - Rahardjo, Monika; Sihombing, Monang; Wulandari, Benedicta Miquella Adisty (Journal of Tropical AgriFood, 2026)
This study investigated the effect of beetroot powder incorporation on the physicochemical, textural, and sensory properties of sourdough bread as part of efforts to develop nutritionally enhanced bakery products with acceptable quality. Four formulations of composite flour of 300 g were prepared: a control (without beetroot powder) and sourdough breads substituion of beetroot powder of 5, 10, and 15%. The physicochemical and textural characteristics were evaluated using texture profile analysis, including hardness, cohesiveness, gumminess, chewiness, adhesiveness, stiffness, and springiness, while sensory attributes were assessed based on appearance, aroma, taste, texture, and overall acceptability. The results demonstrated that increasing beetroot powder levels significantly affected most textural parameters. The highest values of hardness (254.79 gf), gumminess (57.75), and chewiness (4.51) were observed in bread with substitutuion with beetroot powder of 15%, indicating a denser crumb structure at 15% substitution level. Cohesiveness and stiffness increased with beetroot addition, whereas springiness generally decreased, suggesting a trade-off between structural rigidity and elasticity of the dough. Sensory evaluation revealed that the control bread achieved higher scores across most attributes; however, the bread with beetroot powder substitution of 10% recorded the highest overall acceptability among the beetroot-enriched breads (3.90 ± 0.84). Moderate beetroot incorporation enhanced the visual appeal and flavor balance without masking the characteristic of the sourdough. However, excessive beetroot substitution negatively affected sensory quality due to the dominant earthy flavor and less desirable texture. In conclusion, 10% beetroot powder substitution provides an optimal balance between nutritional enhancement, textural quality, and consumer acceptance, offering valuable insights for the formulation of functional sourdough bread products.